Critical Review: A Review of the Studies About the Usage of Social Media During the Covid-19 Pandemic - Cheng, Cheng (2021)
Since the coronavirus disease (covid-19) was declared a public health emergency of international concern by the World Health Organization in January 2020, it has led to the loss of millions of human lives and a global economic recession. Recently, there has been a recognized need for effective health communication via social media to deliver accurate information and promote pertinent behavioral change. Thus, this study provides a systematic review to explore what has been done, what conflicts exist, and what knowledge gap remains in terms of social media use during the covid-19 wave, indicating relevant communication strategies. This research is based on 76 relevant papers taken from searches on the Web of Science and Google Scholar. The analysis revealed that much of the literature confirms the positive effect of social media on information propagation and promotion of precautions in the control of covid-19. The spreading of rumors, especially about government performance, in social media is clearly of increasing concern. Currently, heated debate continues about the association between exposure to social media and public mental health. Another fiercely debated question is whether rumors are shared more widely than fact-checking information. Up to date, far too little attention has been paid to information disparities and vulnerable groups on social media.